Financialization as a Factor Constraining Economic Growth and Standard of Living Improvement in Poland - Księżyk, Marianna; Michalski, Marek (Managerial Economics, 2012)
Despite evidence of numerous negative effects of the process of financialization in open markets and under globalization, in Poland, there is a lack of interest in reliable, documented empirical research on the sources and causes of financialization and its impact on economic growth and living standards of all residents. Recognizing these problems as important for the realization of objectives that were at the foun- dation of European integration, sources of financialization and its implications for economic growth and living standards of residents of Poland, as an EU country, were characterized. The state of theory in this area was assessed and the results of empirical research that was conducted were presented.